Existential Drift: a Literature Review on the Role of Meaning in Workplace Boredom - Fanya Izmi Hawa; Lussy Dwiutami Wahyuni; Anna Armeni Rangkuti; Zarina Akbar (Department of Psychology, Faculty of Education, Universitas Negeri Surabaya, 2025)
This literature review explores the phenomenon of boredom in the workplace, linking it with existential theory through the lens of positive psychology. It introduces the concept of existential drift—a gradual psychological disengagement that occurs when individuals lose a sense of meaning in their work. Using a structured literature review approach, this study synthesizes findings form 22 scholarly sources to explore how perceived meaning shapes, mitigates, or exacerbates boredom at work. Th review finds that boredom is not merely caused by task monotony, but often emerges from a deeper sense of meaninglessness. Meaningful work is shown to buffer against boredom, while its absence can lead to both maladaptive and adaptive coping strategies. The review highlights the importance of meaning regulation and proposes existential drift as a key framework to understand persistent disengagement in work settings. These findings suggest that organizations should foster meaning-making processes to support employee well-being and engagement.